Development of entrepreneurship education based on the menara berkah model in Indonesian vocational high schools - Sari, Maya Novita; Harto, Slamet Prawiro; Muhyadi, Muhyadi (Journal of Education and Learning (EduLearn), 2024)
Soft skills-based learning is very important to equip vocational high school students, one of which is entrepreneurship. This research aims to develop entrepreneurship learning through the menara berkah model. This research aims to develop entrepreneurship learning through the Menara Berkah model. This research is a type of development research including pre-development stage of the model, model development, and validation or model testing stage. The research sample amounted to 25 people from two vocational high schools in Palembang and Yogyakarta. While data collection techniques using mixed methods and data analysis using statistical tests. Based on the construct of the model content assessment results obtained an average of 4.45, this score indicates that all aspects are components that are feasible to be used as material or content of entrepreneurship-based learning management models in the catering expertise competency. The Menara Berkah model is proven to be effective and applicable, with an average achievement of 4.76%, this indicates that this model can be used and can make it easier, especially in entrepreneurship-based learning. The results also show six competencies that must be possessed by students, namely: technical skills, decision making, organizational skills, marketing and financial management, risk taking, creativity, and innovation.